Development of an AI based e-module to improve ICT learning outcomes in package B - Ritno Ritno; Lili Dasa Putri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study addressed low learning outcomes and limited engagement in ICT subjects among adult learners in the Package B nonformal education program at PKBM Bintang Selatan Bersatu, Pesisir Selatan Regency. A Research and Development approach with a Design-Based Research orientation was employed to develop an AI-based e-module integrating adaptive feedback, interactive content, and personalized learning pathways. Thirty-seven seventh-grade learners participated through purposive sampling. Data were collected via expert validation sheets, practicality questionnaires for tutors and learners, observation checklists, and pre-test/post-test assessments. Results showed high validity scores from experts, positive learner and tutor responses on usability and engagement, and significant improvement in learning outcomes (paired t-test, t(36)=11.27, p<0.05; N-Gain=0.49, moderate gain). Findings indicate that AI-supported features effectively enhanced conceptual understanding while supporting independent learning, although intervention duration and participants’ prior knowledge limited maximal gains. The study concludes that AI-based e-modules are a feasible and practical innovation for nonformal ICT learning, with potential for further refinement and long-term implementation.